STUDY OF THE MECHANISM OF OXYCHLORINATION OF ETHYLENE-PROPYLENE ELASTOMER - Dr Ayralova Tamara; Yusifli Nazakat Sabuhi (World Scientific Reports, 2026)
Ethylene-propylene copolymers posses high chemical resistance, elasticity, and durability against environmental factors. However, their modification-specifically through the oxyclorination method opens opportunities for the targeted alteration of their properties, thereby expanding their potential for industrial application. In light of increasing requirements for environmental safety, the development of energy-efficient and ecologically safe oxychlorination methods is of particular importance. Researching the oxychlorination processes of ethylene-propylene based organic compounds contributes to the advancement of scientific understanding and the creation of novel materials. This article examines the mechanism of oxidative chlorination of ethylene-propylene elastomers.